2015
DOI: 10.5603/fhc.a2014.0035
|View full text |Cite
|
Sign up to set email alerts
|

Protein and siRNA delivery by transportan and transportan 10 into colorectal cancer cell lines

Abstract: Introduction. Cell penetrating peptides (CPPs) have the ability to translocate through cell membranes with high efficiency and therefore can introduce biological agents with pharmaceutical properties into the cell. Transportan (TP) and its shorter analog transportan 10 (TP10) are among the best studied CPPs, however, their effects on viability of and cargo introduction into colorectal cancer (CRC) cells have yet not been investigated. The aim of our study was to evaluate the cytotoxic effects of TP and TP10 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…Cell-penetrating sequences such as transportan-10 (TP-10) and transportan (TP) have recently been evaluated by Wierzbicki et al Biotinylated analogues of TP and TP-10 have demonstrated an endocytosis-independent and highly efficient delivery of siRNA when complexed with streptavidin in HCT116 (metastatic CRC model) and HT29 (early stage CRC model) cell lines and resulted in a high silencing activity of SASH-1 mRNA. [76] It can clearly be inferred that streptavidin provides a substantial advantage for cellular and tissue internalization in addition to its use as a dynamic stoichiometric support (back-bone) for nanocomplexes.…”
Section: Applications In Nanoscale Delivery Systemsmentioning
confidence: 99%
“…Cell-penetrating sequences such as transportan-10 (TP-10) and transportan (TP) have recently been evaluated by Wierzbicki et al Biotinylated analogues of TP and TP-10 have demonstrated an endocytosis-independent and highly efficient delivery of siRNA when complexed with streptavidin in HCT116 (metastatic CRC model) and HT29 (early stage CRC model) cell lines and resulted in a high silencing activity of SASH-1 mRNA. [76] It can clearly be inferred that streptavidin provides a substantial advantage for cellular and tissue internalization in addition to its use as a dynamic stoichiometric support (back-bone) for nanocomplexes.…”
Section: Applications In Nanoscale Delivery Systemsmentioning
confidence: 99%
“…On the other hand, there is a chimeric galanin-mastoparan peptide called transportan, which contains the first 13 amino acids from the highly conserved amino-terminal part of galanin and the 14 amino acids sequence of mastoparan in the carboxyl terminus [ 179 ]. Transportan and some derivatives have the capacity to carry macromolecules [ 180 , 181 , 182 ].…”
Section: Wasp Venommentioning
confidence: 99%
“…The role of the linker is often attributed to side chains of the residues present in CPP amino acid sequence, such as the thiol group of cysteine or the e-amino group of lysine. Non-covalent interactions, such as between streptavidin and biotin attached to CPP, are also possible [45].…”
Section: Methods Of Cpp Conjugation With Transported Moleculesmentioning
confidence: 99%
“…Hence, cell biology techniques were used to determine the type of endocytosis contribution or the transport without energy contribution in the process of CPP absorption: -incubation of cells with CPPs at low temperatures (< 4°C) or under energy deficiency; -application of trypsin to remove surface receptor proteins; -use of confocal or freeze-fracture electron microscopy [43,44]; -incubation with compounds facilitating selective transport pathway, e.g. brefeldin A [45]; -binding to a cargo molecule determining a specific type of transport (e.g. transferrin, cholera toxin, dextran, or G protein) or to the target location in the cell allowing the determination of internalization type (e.g.…”
Section: Energy-dependent Endocytosis-mediated Cellular Uptakementioning
confidence: 99%